2020
DOI: 10.1111/idj.12577
|View full text |Cite
|
Sign up to set email alerts
|

Does second-hand smoke associate with tooth loss among older Japanese? JAGES cross-sectional study

Abstract: Objective: Secondhand smoke (SHS) is considered a risk factor for a number of oral diseases. However, its influence on tooth loss, which is the final consequence of periodontal disease and caries, remains unknown. We aimed to evaluate the association between SHS experience and the number of remaining teeth among non-smoking older Japanese individuals. Methods: Cross-sectional data from the Japan Gerontological Evaluation Study (JAGES) 2013 were used. From the 27,561 people ≥65 years of age who responded to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Therefore, in the multivariate analysis adjusted for age, exposure to secondhand smoke was negatively associated with the number of teeth. Similar negative confounding was observed in a previous study that also examined the association between exposure to secondhand smoke and the number of teeth 13 . The study found, through univariate analysis, that older people with frequent exposure to secondhand smoke had a higher number of teeth; however, multivariate analysis adjusted for age and other confounders showed a negative association between exposure to secondhand smoke and the number of teeth.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, in the multivariate analysis adjusted for age, exposure to secondhand smoke was negatively associated with the number of teeth. Similar negative confounding was observed in a previous study that also examined the association between exposure to secondhand smoke and the number of teeth 13 . The study found, through univariate analysis, that older people with frequent exposure to secondhand smoke had a higher number of teeth; however, multivariate analysis adjusted for age and other confounders showed a negative association between exposure to secondhand smoke and the number of teeth.…”
Section: Discussionsupporting
confidence: 84%
“…It is well known that smoking has a profound exacerbating effect on the major causes of tooth loss 10 - 12 . Not just active, but secondhand smoking also has harmful effects on oral health, causing tooth loss 13 , 14 , severe periodontitis 15 , dental caries 16 , and gingival pigmentation 17 . Exposure to secondhand smoke results in the involuntary inhalation of the same harmful substances (nicotine, tar, carbon monoxide, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Second-hand smoke (SHS), in which people breathe in smoke exhaled by smokers, is also considered as a risk factor for oral diseases, including the increased risk for periodontal disease [ 51 , 52 , 53 ]. A study in Japan [ 54 ] evaluated the association between SHS experience and the number of remaining teeth among nonsmoking Japanese individuals, specifically in an older population aged 65 years. The data of 18,865 respondents who had never smoked were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The data of 18,865 respondents who had never smoked were analyzed. The study found that daily SHS was related with fewer remaining teeth, with an odds ratio for having no teeth rather than having more than 20 teeth of 1.35 ( p < 0.01) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 11 ] also said that secondhand smoking is relevant to mental health conditions, such as depression, stress, and suicide. One percent of the total mortality rate is likely to be associated with SHS every year, and it is very important to limit secondhand smoking to improve public health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%